Seleção de liga de alumínio para aplicação em motor de automodelo - Carvalho, Luisa Coelho de (Universidade Federal de São Carlos, 2024)
Remote control car modeling is gaining increasing prominence nowadays. The lack of manufacturers in Brazil for combustion engine model car pistons requires a refined selection of materials to obtain the best material for this application. There is a lack of information in literature, standards, and patents for accessories of combustion engine model cars. The theoretical material selection is compared with experimental data. An experimental investigation was conducted through chemical analysis using Energy Dispersive X-ray Spectroscopy (EDS) and microstructural analysis using Optical Microscopy of a model car piston manufactured in Italy. Two chemical analyses yielded results inconsistent with the observed microstructure. The microstructure reveals a piston composed of a hypoeutectic aluminum-silicon alloy. The hardness obtained of 132HV corresponds to a hypoeutectic aluminum-silicon alloy and complies with the ABNT NBR15905 standard for conventional automobile pistons. A material selection conducted in the Granta Edupack 2020 software revealed aluminum-silicon alloys, specifically the cast alloys of the 3XX.X series, as suitable candidates for this application.
Selection of aluminum alloy for use in model car engine
Keywords: Pistões de automodelos; Seleção de materiais; Ligas de alumínio-silício; Car modeling pistons; Materials selection; Al-Si alloys; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA